English spelling for EFL students - López Rua, Paula (Colección de libros electrónicos en Xebook, 2013)
This manual provides both intermediate and advanced level students of English as a Foreign Language with further knowledge and practice so as to make them improve their spelling skills. The book is divided into six chapters, and its contents are based on the analysis of a corpus of spelling errors spotted in exams, essays and exercises done by Spanish university students. The manual can be used for self-study, since it also includes an answer key at the back, where students can check the correct or suggested answers to all the exercises.